Uremic stomatitis mimicking oral squamous cell carcinoma associated with local and systemic factor - Ridho, Faiznur; Hasanah, Novia Tri; Dewi, Tenny Setiani (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Uremic stomatitis is one of the oral manifestations of chronic kidney disease. This disease is caused due to increased levels of urea in the blood circulation. Patients will complain sore lesions accompanied by a characteristic ammonia breath odor. The clinical manifestation of uremic stomatitis is not only influenced by high levels of urea in the blood but also related to local factors, the oral anatomy and parafunction habits. This study aimed to present a case report of clinical features of uremic stomatitis that mimicking oral squamous cell carcinoma. A 51 year old woman was referred from the department of internal medicine to the department of oral medicine at Hasan Sadikin Hospital, Bandung. The patient complained of pain in the tongue and also when swallowing. The clinical manifestation shows an ulcerated lesion on the right lateral of the tongue and a slightly raised hyperkeratotic area on the floor of the mouth. The treatment is using 0.12% chlorhexidine digluconate mouthwash three times a day and followed by applying a thin layer of vaseline on the upper and lower lips, as well as instructions and education on maintaining oral and tongue hygiene. Controls were carried out on the second and fourteenth day. The patient complaints are decreasing until disappear. The patient's masticatory function is getting better. Local and systemic factors have effect on the clinical manifestation of uremic stomatitis. A clinician must be able to carry out examinations, establish diagnosis and appropriate management so that patients receive appropriate treatment.